Governing the mixed health workforce: learning from Asian experiences. Issue 2 (7th April 2017) - Sheikh, Kabir; Josyula, Lakshmi K; Zhang, Xiulan; Bigdeli, Maryam; Ahmed, Syed Masud
Abstract : Examination of the composition of the health workforce in many low and middle-income countries (LMICs) reveals deep-seated heterogeneity that manifests in multiple ways: varying levels of official legitimacy and informality of practice; wide gradation in type of employment and behaviour (public to private) and diverse, sometimes overlapping, systems of knowledge and variably specialised cadres of providers. Coordinating this mixed workforce necessitates an approach to governance that is responsive to the opportunities and challenges presented by this diversity. This article discusses some of these opportunities and challenges for LMICs in general, and illustrates them through three case studies from different Asian country settings.